Analisis Pengamanan dan Pemanfaatan Tanah Desa Berdasarkan Peraturan Desa Sapta Mulia Nomor 14 Tahun 2017 Tentang Pedoman Pengelolaan Aset Desa (Studi di Desa Sapta Mulia Kecamatan Rimbo Bujang Kabupaten Tebo) - Asrai Maros; Hasdani Hasdani; Hafid Zakariya (Wajah Hukum, 2020)
The purpose of this research is to analyze the security and distribution of village cash land based on the regulation of sapta mulia village, The research method used is an empirical juridical method the results of the research show that the safeguard and utilization has not been running in accordance with Sapta Mulia Village Regulation No. 14 of 2017. For administrative safeguards it was found that the village land assets did not yet fully have documents or archives supporting the legitimate administration, for the protection of the land law the village was new in the form of a land deed and did not have a valid land certificate of ownership, and for physical security it was found that no attempt to install a placemark or peg and name board ownership of the village's land assets made vulnerable to claims by other parties. On the utilization side such as the utilization of land in the form of leases, it was found that for the leasing of the village land was not done in writing and it was still found that many communities had expired their leases but they did not renew the lease. For the utilization of land in the form of borrowed use, it was found that for the loan of use has not been implemented at all, while for the utilization of land in the form of cooperation, it was found that there has been no cooperation in engaging other parties to manage the land, and researchers assessed the Sapta Mulia Village Government in creating cooperation with third parties seemed lacking initiative and innovation so that the land could not be utilized as it should be.